THE EFFECT OF GDP, EXCHANGE RATE, AND INTEREST RATE ON PROFIT SHARING INCOME OF MUDHARABAH FINANCING AT ISLAMIC BANKS - Ifan Nur Hidayat; Radia Purbayati (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2023)
This study aims to explain the influence of macroeconomic factors such as gross domestic product (GDP), exchange rates, and interest rates (BI Rate) on revenue sharing from mudharabah financing at Islamic Banks in Indonesia for 2016-2020. The sample selection in this study used purposive sampling with 9 selected samples from the total population of 14 Islamic Banks in Indonesia. The data used in this study are secondary data obtained from annual reports published by each Islamic Bank in the 2016-2020 period. The analytical method used in this research is panel data regression using EVIEWS 10 software and obtained the fixed effect model as the best estimation model. Based on the study's results, partially gross domestic product (GDP) and interest rates (BI Rate) have no significant effect on revenue sharing for mudharabah financing. In contrast, the exchange rate negatively and significantly impacts revenue sharing for mudharabah financing. In addition, simultaneously, the results of gross domestic product (GDP), exchange rates, and interest rates (BI Rate) significantly affect revenue sharing for mudharabah financing.